Endemic, epidemic and pandemic infections: the roles of natural and acquired herd immunity. Issue 3 (20th June 2023) - Stevens, Dennis L.; Bryant, Amy E.
Abstract : Purpose of review: This review summarizes the general concepts of innate and acquired immunity, including vaccine use and hesitancy, as they relate to reduction of the global burden of highly communicable infectious diseases. Recent findings: Vaccination to increase herd immunity remains the cornerstone of disease prevention worldwide yet global vaccination goals are not being met. Modern obstacles to vaccine acceptance include hesitancy, reduced altruistic intentions, impact of COVID-19, distrust of science and governmental agencies as well as recent geopolitical and environmental disasters. Together, such barriers have negatively impacted immunization rates worldwide, resulting in epidemics and pandemics of serious life-threatening infections from vaccine-preventable diseases, especially those affecting children. In addition, pathogens thought to be controlled or eradicated are reemerging with new genetic traits, making them more able to evade natural and acquired immunity, including that induced by available vaccines. Lastly, many serious and widespread infectious diseases await development and utilization of efficacious vaccines. Summary: The global burden of communicable diseases remains high, necessitating continued pathogen surveillance as well as vaccine development, deployment and continued efficacy testing. Equally important is the need to educate aggressively the people and their leaders on the benefits of vaccination to the individual, local community and the human population as a whole.